Studi Kasus Merger Sekolah Dasar Negeri : Solusi Mikro Efisiensi Anggaran Pendidikan Dan Krisis Guru - Rahmat, Asep; Subagyo, Ahmad (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2025)
This research report presents an analysis of the budget efficiency policy implemented by the President of the Republic of Indonesia and its impact on teacher availability in public elementary schools. Using qualitative narrative methods, the study highlights how school mergers (regrouping) can serve as an effective micro-strategy to address the teacher shortage crisis while simultaneously achieving budget efficiency at the local level. The discussion focuses on various aspects of efficiency resulting from mergers, including streamlining administration, reducing operational costs, optimizing teacher redistribution, and improving the quality of education and utilization of facilities. The report also identifies the impacts and challenges of implementing the merger policy, concluding with comprehensive conclusions and policy recommendations.